Data Structures and Algorithms with the C++ STL. - John Farrier; PACKT (GB: Packt, 2024)
Explore the C++ 23 STL with practical guidance on vectors, algorithms, and custom types for intermediate developers, enriched by real-world examples. Key Features Master the std::vector and understand why it should be your default container of choice Understand each STL algorithm and its practical applications Gain insights into advanced topics such as exception guarantees and thread safety Purchase of the print or Kindle book includes a free PDF eBook Book Description While the Standard Template Library (STL) offers a rich set of tools for data structures and algorithms, navigating its intricacies can be daunting for intermediate C++ developers without expert guidance. This book offers a thorough exploration of the STL's components, covering fundamental data structures, advanced algorithms, and concurrency features. Starting with an in-depth analysis of the std::vector, this book highlights its pivotal role in the STL, progressing toward building your proficiency in utilizing vectors, managing memory, and leveraging iterators. The book then advances to STL's data structures, including sequence containers, associative containers, and unordered containers, simplifying the concepts of container adaptors and views to enhance your knowledge of modern STL programming. Shifting the focus to STL algorithms, you'll get to grips with sorting, searching, and transformations and develop the skills to implement and modify algorithms with best practices. Advanced sections cover extending the STL with custom types and algorithms, as well as concurrency features, exception safety, and parallel algorithms. By the end of this book, you'll have transformed into a proficient STL practitioner ready to tackle real-world challenges and build efficient and scalable C++ applications. What you will learn Streamline data handling using the std::vector Master advanced usage of STL iterators Optimize memory in STL containers Implement custom STL allocators Apply sorting and searching with STL algorithms Craft STL-compatible custom types Manage concurrency and ensure thread safety in STL Harness the power of parallel algorithms in STL Who this book is for This book is for intermediate-level C++ developers looking to enhance their software development skills. Familiarity with basic C++ syntax and object-oriented programming (OOP) as well as some exposure to data structures and algorithms is assumed. Tailored to software engineers, computer science students, and hobbyist programmers, this book delves into C++ STL for practical application, performance enhancement, and efficient coding practices.
Data in extended ASCII character set.
Mode of access: Internet.